HUBUNGAN PENGETAHUAN, SIKAP DAN PARTISIPASI PEDAGANG DALAM PENGELOLAAN SAMPAH DI PASAR - Samuel Marganda Halomoan Manalu; Deli Syaputri; Risnawati Tanjung; Theodorus Teddy Bambang Soedjadi (Poltekkes Kemenkes Medan, 2023)
Waste generated from market activities is one of the main sources of waste generation and has become a big problem coupled with the knowledge, attitudes and participation of traders who do not really support good waste management because they throw garbage anywhere and without distinguishing between organic and inorganic waste. . The knowledge, attitudes, and participation of traders who do not support waste management are a reflection of their ignorance of the environment. This research is an analytic survey study designed with a cross sectional design. Research data were collected through interviews using a questionnaire and observation using a checklist to 60 samples. Through the research, the following results were obtained: 34 respondents (64.7%) had a low level of knowledge, 26 respondents (35.3%) had a high level of knowledge; 31 respondents (51.7%) had attitudes in the low criteria regarding waste management, and 29 respondents (48.3%) had attitudes in the high criteria; 29 respondents (48.3%) had low participation in waste management, and 31 respondents (51.7%) had high participation. Through the results of the chi-square test, it is known that there is a correlation between the level of knowledge of traders and waste management (p value 0.008), a correlation between merchant attitudes and waste management (p value 0.010), and a correlation between merchant participation and waste management (p value 0.000).